Probing carboxylic acid groups in replaced and mixed self-assembled monolayers by individual ionized dendrimer molecules : an atomic force microscopy study - Wiesler, U. M. (2012)
Polyphenylene dendrimer molecules, G2Td(COOH)16, were ionized (G2 ions) and then adsorbed on a carboxylic acid (COOH) group terminated self-assembled monolayer (SAM) on a Au substrate through the linkage with Cu2+ ions. The individual G2 ions were observed by noncontact atomic force microscopy (NCAFM). The strong interaction between the G2 and Cu2+ ions, the latter of which are preadsorbed on the COOH SAM, led to a compression or deformation of the SAM and resulted in a decreased height of the G2 ions measured by NCAFM as compared to a theoretical model of the dendrimer molecules. The present method offers an approach to bind dendrimer molecules to a solid substrate and to study the nanoscale behavior of two kinds of thiol molecules in replaced and mixed SAMs.